International banking : innovations and new policies - Iffiland, Charles; Languatin, Pierre; Mikdashi, Z. (London : Macmillan, 1988)
This compendium on international banking is based on the colloquium held on the occasion of the 75th anniversary of the Ecole des Hautes Etudes Commerciales (HEC) of Lausanne on 6 - 7 June 1986.
Includes index
osc 20/9/17
Loans
Keywords: Banking